Central banks sowing the seeds for a green financial sector? NGFS membership and market reactions - Lion Fischer; Marc Steffen Rapp; Johannes Zahner (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2024)
In December 2017, during the One Planet Summit in Paris, a group of eight central banks and supervisory authorities launched the "Network for Greening the Financial Sector" (NGFS) to address challenges and risks posed by climate change to the global financial system. Until 06/2023 an additional 69 central banks from all around the world have joined the network. We find that the propensity to join the network can be described as a function in the country's economic development (e.g., GDP per capita), national institutions (e.g., central bank independence), and performance of the central bank on its mandates (e.g., price stability and output gap). Using an event study design to examine consequences of network expansions in capital markets, we document that a difference portfolio that is long in clean energy stocks and short in fossil fuel stocks benefits from an enlargement of the NGFS. Overall, our results suggest that an increasing number of central banks and supervisory authorities are concerned about climate change and willing to go beyond their traditional objectives, and that the capital market believes they will do so.
Keywords: E58; E61; G1; Q54; Q58; 330; Climate finance; green central bank policy; stock market reaction; sustainable finance